Multiphysics modeling for bone remodeling simulation: A methodological framework (2017)
In the present study an object oriented integrative modeling methodology is proposed for the construction of synthetic, computational models of bone-bone environment system that allow its simulation under in vivo conditions. The analytical mathematical approach to model and study ordinary materials will be outlined, indicating its limitations when dealing with biomaterials in physiological environments. The proposed object oriented integrative modeling will be explained emphasizing its advantages and possibilities. Finally, the architecture of the "in vivo" modeling and simulation software framework is shown, described and explained indicating further work based on this framework.